Adrenal Hemorrhage in a Cortisol-Secreting Adenoma Caused by Antiphospholipid Syndrome Revealed by Clinical and Pathological Investigations: A Case Report - Ochi, Kentaro; Abe, Ichiro; Yamazaki, Yuto; Nagata, Mai; Senda, Yuki; Takeshita, Kaori; Koga, Midori; Yamao, Yuka; Shigeoka, Toru; Kudo, Tadachika; Fukuhara, Yuichiro; Miyajima, Shigero; et al. (Frontiers in Endocrinology, 2022)
Due to its rarity, adrenal hemorrhage is difficult to diagnose and its precise etiology has remained unknown. One of the pivotal mechanisms of adrenal hemorrhage is the thrombosis of the adrenal vein, which could be due to thrombophilia. However, detailed pathological evaluation of resected adrenal glands is usually required for definitive diagnosis. Here, we report a case of a cortisol-secreting adenoma with concomitant foci of hemorrhage due to antiphospholipid syndrome diagnosed both clinically and pathologically. In addition, the tumor in this case was pathologically diagnosed as cortisol-secreting adenoma, although the patient did not necessarily fulfill the clinical diagnostic criteria of full-blown Cushing or sub-clinical Cushing syndrome during the clinical course, which also did highlight the importance of detailed histopathological investigations of resected adrenocortical lesions.